RANCANG BANGUN WEBSITE PELANGGAN PT MEGA ARTHA LINTAS DATA UNTUK PEMILIHAN PAKET INTERNET DAN PEMBAYARAN - Hardiansyah, Aria Mubaroq; Budiman (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2025)
Advances in information technology have encouraged companies to transform themselves into more efficient and practical digital services. PT Mega Artha Lintas Data's Majalengka branch still uses manual methods to manage internet package selection and payments, making it prone to recording errors and verification delays. This study aims to design and build an e-business website as a means of digitizing customer services, particularly in selecting internet packages and paying bills. The development method used is the Waterfall model with stages of requirements analysis, design, implementation, and testing. The website was developed using HTML, CSS, and JavaScript for the interface and integrated with the Midtrans payment gateway as a digital payment simulation. The implementation results show that the website is capable of displaying internet package information, providing transaction pages, and validating payments through pop-up notifications. Testing using the Blackbox Testing method shows that the main features work as designed. This research has produced an e-business website design that can improve customer service efficiency, although further development is still needed, such as the addition of an internal database and back-end integration, so that it can be fully implemented in company operations.